Clonagem, expressão heteróloga e caracterização parcial da trealase periplasmática de Xanthomonas citri subsp. citri e do seu envolvimento com a fitopatogenicidade - Alexandrino, André Vessoni (2015)
Citrus canker imposes damages to citriculture by causing drop in productivity and fruit quality and the absence of effective control and cure. Thus, the economic potential of citrus is limited in part by this disease mainly caused by the bacterium Xanthomonas citri subsp. citri (XAC) that presents the greatest virulence and broad spectrum of citrus hosts, compared to bacteria Xanthomonas fuscans subsp. aurantifolii types B (XauB) and C (XauC). In a proteomic analysis previously performed by our research group, periplasmic trehalase was identified as a protein which expression differed between XAC e XauC in an in vitro induction of pathogenicity. Trehalase is an enzyme that catalyzes hydrolysis reaction of trehalose, a disaccharide composed of two glucose units, which role in the plant-pathogen interaction is poorly understood. One of the objectives of the study was to obtain this enzyme in purified form using an IPTG-inducible heterologous expression system in E. coli, for purposes of partial characterization of its structure and activity. The recombinant XAC periplasmic trehalase is a monomer bearing wide pH stability and showed Michaelian kinetics. The Michaelis-Menten constant (Km) for trehalose was 0,124 ± 0,015 mM and Vmax 17,319 ± 0,035 μMol glucose.min-1.mg protein-1 . Circular dichroism spectroscopy indicated the following composition of secondary structures: 42.7% α-helices and 13% β-sheets. A gene knockout method based on double homologous recombination between the genomic DNA and suicide vector pNPTS138 has made possible to obtain a strain deleted in the gene encoding the periplasmic trehalase (XACΔ0604), which enabled to evaluate the relationship between this gene and the XAC pathogenicity in Citrus aurantifolia. Infiltrated leaves with XACΔ0604 showed drenching and necrosis of plant tissue and intense brownish pustules compared with wild XAC, suggesting greater virulence of the mutant strain. The periplasmic trehalase activity was compared in XAC and XauC cell extracts from two culture mediums, non-pathogenicity-inducing (CN) and pathogenicity-inducing (XAM-M). Interestingly, XauC has showed higher enzyme activity compared to XAC in XAM-M. Thus, the noticeable higher XACΔ0604 pathogenicity and the greater activity of XauC periplasmic trehalase compared to XAC are indicatives that trehalose may promote pathogenicity.